Performance of exporting shrimps and dry fishes from Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
This study shows the present status of exporting shrimps and dry fishes from Bangladesh in the pre-and -post liberalization period, estimates the growth rate and instability of exporting shrimps and dry fishes for earnings, quantity & price for five years. Recent status presents that farming of shrimp and processing of dry fish are increasing over the year. Status of exporting shrimp & dry fish (value, volume & price) are decreasing in recent years compared to previous years. The overall estimated growth of exported shrimp and dry fish (value) were found 19.48% and 16.53% and (volume) were found 11.52% and 12.86%, respectively. On the other hand, overall estimated export growth of shrimp & dry fish (price) were 175.94% and 37.58%, respectively. Instability in shrimp export earnings was found the highest in period I which was 62.16% and the lowest in period II which was 12.56%. Dry fish export instability was the highest for period I which was 128.08% & the lowest percentage was 54.49% in period II. Instability in quantity export of shrimp was found the highest in period I at 63.29% whereas it was 155.92% in period I for dry fish export and the lowest percentage for both were 14.5% & 48.66% in period II, respectively. On the other hand, instability in prices of exported shrimp & dry fish were found the highest in period I which were 25.26% & 140.63%, respectively. The lowest percentage for shrimp in period II which was 11.29% and for dry fish it was 63.56% in period III. It also affects export of shrimp & dry fish from Bangladesh. The circumstances of shrimp & dry fish export demand different institutional supports to enhance the marketing activities and to strengthen the competitive position in the international market with a view to ensuring more contribution to our economy.J. Bangladesh Agril. Univ. 14(1): 69-74, June 2016